Analisis Pengaruh Perilaku Konsumtif, Motivasi, Kelompok Referensi dan Kualitas Layanan Terhadap Keputusan Menabung - Melina Agustina Rahayu; Mustika Widowati; Jati Handayani (Al Maal: Journal of Islamic Economics and Banking, 2021)
This study analyze and obtain empirical evidence about the effect of Consumptive Behavior, Motivation, Reference Group and Service Quality on the Decisions of Saving at PT Bank Tabungan Negara (BTN) Branch Office Sharia Semarang either simultaneously or partially. The population of this research is the customers of PT Bank Tabungan Negara (BTN) Branch Office Sharia Semarang. Sample technique used is purposive sampling and accidental sampling technique, there are 135 respondents who meet the criteria. The analysis model used in this study is a multiple linier regression analysis model. The analysis technique uses F test, Determination Coefficient Test (R2), and t test which is processed using SPSS 16 program. The results of proving the hypothesis and discussion in this study indicate that (1) Consumptive Behavior, Motivation, Reference Group and Service Quality simultaneously have a significant impact on saving decisions (2) Consumptive Behavior partially has no significant effect on saving decisions. (3) Motivation partially has a significant effect on saving decisions. (4) The reference group partially does not significantly influence on saving  decisions. (5) Service quality partially has significant effect on savinng decisions.